2004
DOI: 10.1038/sj.onc.1208276
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin strongly inhibits growth and survival of human endothelial cells via cell cycle arrest and downregulation of survivin, Akt and NF-κB: implications for angioprevention and antiangiogenic therapy

Abstract: Recently, we observed that suppression of tumor xenograft growth by silibinin was associated with reduction in tumor vasculature and an increased apoptosis. Here, we provide evidence for molecular events associated with antiangiogenic efficacy of pharmacologically achievable doses of silibinin in endothelial cell culture system. Our data show that silibinin almost completely (Po0.001) inhibits growth of human umbilical vein endothelial cells (HUVEC) and human microvascular endothelial cells (HMVEC-dermal origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 64 publications
(64 reference statements)
4
100
2
Order By: Relevance
“…Some reports have documented that silibinin inhibits Akt phosphorylation (23,38). However, in our study, silibinin was found to induce the activation of the prosurvival kinase Akt in MCF-7 breast cancer cells (Fig.…”
Section: Translation Inhibition By Silibinincontrasting
confidence: 50%
See 1 more Smart Citation
“…Some reports have documented that silibinin inhibits Akt phosphorylation (23,38). However, in our study, silibinin was found to induce the activation of the prosurvival kinase Akt in MCF-7 breast cancer cells (Fig.…”
Section: Translation Inhibition By Silibinincontrasting
confidence: 50%
“…Treatment of cells with silibinin has also been shown to inhibit expression of Mcl-1 and survivin (23,24), two eIF4E-responsive genes (25,26). Identification of other mRNAs, the translation of which may be affected by silibinin, will require more intensive microarray analysis of transcripts in polysomes of silibinin-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that silibinin possesses antioxidant, antiapoptotic, anti-inflammatory and anti-fibrotic properties (1)(2)(3). However, the effects of silibinin on type I collagen expression in human skin fibroblasts (HSFs) and the related signaling pathways remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Non-cytotoxic effect of silibinin on human skin fibroblasts. Cells were plated at a density of 4x10 3 /cm 2 in 96-well plates. Cells were cultured with or without silibinin for 2 days.…”
Section: Effect Of Silibinin On Smad2 and Smad3 Expression In Hsfsmentioning
confidence: 99%
“…The G 2 cell cycle arrest could be caused by DNA damage [60], which activates the so called "G 2 checkpoint", preventing cells from proceeding into mitosis, with a consequent accumulation of cells in the G2 phase. It is interesting to note that the anti-angiogenic drugs proposed for anti-cancer therapy alter endothelial cell cycle either inducing a G 0 or a G 2 arrest [61][62][63], thus confirming the potential for artemisinins as anti-angiogenic drugs.…”
Section: Discussionmentioning
confidence: 99%